(untitled) - Nguyễn, Trường Sinh (Hà Nội, 2006)
This book is formatted nicley. One can just follow the step by step examples in the tutorials from beginning to end. Also, the provided case studies at the end of each chapter further reinforces what was learned within that chapter (if one attempts to do them). It makes the whole idea of designing web pages seem simple
Keywords: Dreamweaver (computer file)